Interpretation of rent's rule for ultralarge-scale integrated circuit designs, with an application to wirelength distribution models. - Lanzerotti, M.Y.
Computer hardware components have changed significantly since the 1960s, 1970s, 1980s, and even since the early 1990s. Work concerning Rent's memos prior to the present paper has been based on a 1971 interpretation of two unpublished memoranda written in 1960 by E. F. Rent while working at IBM, even though today's computer components are significantly different from those in 1960 and 1971. However, because of the significant changes in the design and implementation of computer hardware components since 1960 and 1971, a new interpretation of Rent's memos is needed for today's components. We have obtained copies of Rent's two memos. In these memos, Rent describes the method that he used to obtain an empirical relationship between properties of the computer hardware components of the IBM 1401 and the IBM 1410 computers. We have studied these memos carefully in order to understand Rent's original intent. Based on our careful reading of these two memos, the personal knowledge of one of us with the 1401 and 1410 computers, and our experience designing ultralarge-scale integrated (ULSI) circuits for high-performance microprocessors, we have derived an historically equivalent interpretation of Rent's memos suitable for today's computer components. The purpose of this paper is to present a new interpretation of the memos and to present an application to wirelength distributions of real ULSI circuitry. In this paper, we will: 1) describe the contents of the memos and Rent's method; 2) provide an historically-equivalent interpretation of Rent's memos for today's computer components; and 3) apply this new interpretation to real ULSI control logic circuitry in the 1.3-GHz IBM POWER4 microprocessor. In this paper, we will show that this new interpretation of the two memos provides improved wirelength distribution models with better qualitative agreement with measurements and more accurate estimates of wirelength distributions and wirelength requirements for real ULSI designs compared with prior methods.
Keywords: IBM 1401 computers; IBM 1410 computers; IBM POWER4 microprocessor; Rent memos; Rent method; Rent rule; ULSI control logic circuitry; Computer hardware components; High performance microprocessors; Ultralarge scale integrated circuit design; Wirelength distribution models